Positioning and Fit in Designing and Executing Qualitative Research. - Zilber, Tammar B.; Meyer, Renate E. (Journal of Applied Behavioral Science, 2022)
In this paper, we aim to help researchers think, design, and execute their empirical journey by mapping the terrain of choices common in qualitative research. We offer a matrix that relates to various dimensions—the level at which to study the phenomenon (level of analysis), types of field materials, time orientation of research and data, the analytic approach, and the unit of data (unit of analysis). This matrix is intended to support making informed decisions that result in specific research designs and the continuous process of reflection as to how these choices open and limit the ability to answer the research question and offer an analytic generalization based on the findings.